Vibration Analysis on Spalling Failure of Gearbox Bearing of High-speed Train - Azhong Zhang; Jianxin Liu; Jiufeng Cai (Jixie chuandong)
In order to study the vibration response of gearbox bearings under fault conditions of high-speed train，based on Hertz contact theory，considering the spalling failure on the outer ring raceway of the bearing，and by using the 3D modeling software SolidWorks and dynamics software RecurDyn，a dynamical model of high-speed train gearbox bearing with spalling fault is established. Through the simulation analysis of the bearing，it can be seen that when the spalling failure on the outer ring raceway occurs，the angular velocity of the roller appears periodic mutation，resulting in slippage. The impact from the failure of the roller and outer ring raceway is transmitted to the cage，which reduces the stability. The vibration acceleration spectrum of the outer ring has peaks at 1 and 2 times the characteristic frequency of the outer ring. According to theoretical analysis，it can be judged that the outer ring is faulty. The contact force between the outer ring and the roller will increase and decrease periodically at the fault.